2012
DOI: 10.1016/j.seizure.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter trial of oxcarbazepine oral suspension monotherapy in children newly diagnosed with partial seizures: A clinical and cognitive evaluation

Abstract: OXC is effective and well-tolerated as monotherapy in children with partial seizures. There was no difference in the effectiveness of OXC between intellectually normal and intellectually impaired children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
4
1
1
Order By: Relevance
“…Regarding the efficacy of the two ASMs, the seizure-free rates in the OXC and LEV groups in our study were relatively higher than those in previous trials, [18][19][20][21] which was probably due to our design bias and shorter follow-up time. Unlike other studies that recruited patients with drug-resistant epilepsy, 22 most hospitals participating in our study were primary hospitals where the majority of patients had epilepsy that was mild or moderate with low frequency of seizures, where intractable epilepsy and complications were relatively rare, resulting in a higher seizure-free rate.…”
Section: Discussioncontrasting
confidence: 77%
“…Regarding the efficacy of the two ASMs, the seizure-free rates in the OXC and LEV groups in our study were relatively higher than those in previous trials, [18][19][20][21] which was probably due to our design bias and shorter follow-up time. Unlike other studies that recruited patients with drug-resistant epilepsy, 22 most hospitals participating in our study were primary hospitals where the majority of patients had epilepsy that was mild or moderate with low frequency of seizures, where intractable epilepsy and complications were relatively rare, resulting in a higher seizure-free rate.…”
Section: Discussioncontrasting
confidence: 77%
“…On the basis of these findings, we can infer that OXC medication should be prescribed to patients with pediatric epilepsy without concern about possible linguistic problems. Eun et al 39 drew similar conclusions, asserting that OXC is an effective anticonvulsant for both adults and children and is safe to use without inducing verbal or cognitive adverse effects.…”
Section: Discussionmentioning
confidence: 83%
“…However, most of these studies were limited to a small number of adult patients. 35 36 37 38 Conversely, studies that included pediatric patients found that OXC had no negative influence on cognitive function, 7 39 and there is a lack of evidence regarding the effects of OXC on linguistic ability. The present study successfully established that OXC treatment does not promote any remarkable adverse effects but rather enhances the pragmatic and discourse aspects, which are crucial in language use.…”
Section: Discussionmentioning
confidence: 99%
“…The approved label mentioned explicitly that "pharmacokinetic/pharmacodynamic (PK/ PD) modeling provided confirmatory evidence of efficacy across all doses." The anti-epileptic oxcarbazepine (Trileptal) was approved as monotherapy in children, based on advanced PK/PD modeling [41] and subsequently confirmed in a clinical trial [42].…”
Section: Other Examples Of Modeling Influencing Regulatory Decisionsmentioning
confidence: 99%